Construction of Women's Beauty in Newspaper Advertisements in Batak Land, North Sumatra, 1940–1945 - Lukitaningsih Lukitaningsih; Halimatun Sakdiah; Mhd. Agung Permana Siregar; Muhammad Fazlan Akbar; Pidia Amelia; Pristi Suhendro Lukitoyo (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This research examines newspapers in North Sumatra that published beauty advertisements, catering to the aesthetic needs of individuals, especially women seeking self-care and beauty enhancement. The study aims to track the development in types and content of cosmetics advertisements and the advertising stages during the period from 1940 to 1945. Employing semiotics and discourse analysis, this research integrates data collection through interviews and analysis techniques to explore advertisements on women's beauty in mass media published in the Batak region of North Sumatra from 1940 to 1945. Advertisements in these media often depict European women, reflecting an ideology that positioned Europeans as inherently superior to natives. Through visual and narrative strategies, cosmetics advertisements propagated a concept of Western beauty to the indigenous population of the archipelago. This article discusses beauty concepts, such as the allure of a slim physique, a prominent nose, and curly hair, as conveyed by pre-independence media advertisements.